2002
DOI: 10.1046/j.1365-2141.2002.03493.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic quality control of oral anticoagulant therapy comparing the short‐acting acenocoumarol and the long‐acting phenprocoumon

Abstract: Summary. To investigate whether the different pharmacokinetics of acenocoumarol (t 1/2 ¼ 11 h) and phenprocoumon (t 1/2 ¼ 140 h) result in a different quality of anticoagulation, we studied patients from the Leiden anticoagulation clinic treated between 1998 and 1999 for more than 16 weeks. Two hundred and twenty-eight pairs were closely matched for indication for oral anticoagulant therapy (OAT), age, sex and date of start of treatment. Four hundred and fifty six patients with 7245 International Normalized Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 23 publications
10
42
1
3
Order By: Relevance
“…These three vitamin K antagonists have different half-lives and previous studies showed that the stability of anticoagulant therapy was better with the longer-acting phenprocoumon than with acenocoumarol. [15][16][17][18][19] A recent study showed better stability in patients treated with warfarin than in patients using phenprocoumon. 22 We performed a subgroup analysis in the group of patients treated with acenocoumarol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These three vitamin K antagonists have different half-lives and previous studies showed that the stability of anticoagulant therapy was better with the longer-acting phenprocoumon than with acenocoumarol. [15][16][17][18][19] A recent study showed better stability in patients treated with warfarin than in patients using phenprocoumon. 22 We performed a subgroup analysis in the group of patients treated with acenocoumarol.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Thirdly, the type of vitamin K antagonist that is used might influence the effect of vitamin K1 supplementation on the achieved stability, because longer acting vitamin K antagonists result in more stable control per se. [15][16][17][18][19] Finally, supplementation with vitamin K1 would only be useful in the clinic if the frequency of clinical endpoints, such as the number of hemorrhages or thrombotic events, is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies in literature are about warfarin, but there are also some studies on acenocoumarol and phenprocoumon (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…An optimal therapeutic effect is obtained by achieving and maintaining constant INRs within therapeutic range (3).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies in about 215,000 patients of these anticoagulation clinics, treated with acenocoumarol and phenprocoumon, showed that in the last few years the percentage of INR values within the therapeutic target range in the first 2 months after the start of the treatment was 62 (median), compared to 74% in the 3-6 months period after initiation and 78% after 6 months, respectively [2]. Another study [3] found that in the first 6 weeks after the start of acenocoumarol the INR values were only in 32.6% of patients and in only 32.4% of the time within the therapeutic target range [4].…”
Section: Introductionmentioning
confidence: 99%